Sustainable urban infrastructure : the prospects and relevance for middle-income cities of the global South - Hyman, Katherine Rose (African Centre for Cities, 2016)
In this thesis, I contribute to the emerging theoretical knowledge of and policy discourse on sustainable urban infrastructure, as a potential solution to the myriad of ecological and socioeconomic developmental challenges, for middle-income contexts of the global south. To understand this under-studied theme better, this dissertation uses three emblematic case studies of utility departments in the City of Cape Town (CCT) - an in-depth study of the Solid Waste Management Department and supporting studies of the Electricity Services Department, and the Water and Sanitation Department - to determine the prospects and relevance of sustainable infrastructure in such contexts. Through an analysis of urban networked infrastructure, I provide novel insight into the underpinning institutional dynamics that reproduce the service delivery model, and highlight how innovative activities that reflect the principles of sustainable urban infrastructure become embedded within institutional practice. Two conceptual frameworks, developed from the literature, have guided the empirical research and the analysis. The first is a heuristic device that enhances our understanding of sustainable urban infrastructure knowledge and discourse. The second offers a way to understand how it is institutionally mediated. Specifically, these conceptual frameworks are applied to the cases to reveal how the CCT's utility departments respond to an emergent crisis within a sector and how they pursue purposive interventions that reflect the sustainable urban infrastructure theory and discourse. The research was carried out over a period of two years and six months, during which I conducted semi-structured and informal interviews, and extensive document analysis.